Debris flows in val trela (valtellina, italy) - Clerici, Alberto; Massaro, Costanza (Italian journal of engineering geology and environment, 2008)
Debris flows have been the object of research for many years and a number of assessment methodologies involving empirical methods or mathematical models have been developed to address the phenomenon. This study examines four debris flows on the southern slope of Cima Doscopà (Val Trela, Upper Valtellina, Italy) with the objective of assessing the predictive capacity of a number of methods in the literature. The study was divided into phases: measurements and sampling of the debris flows; laboratory tests on the samples; application of empirical formulas to the measurements to determine magnitude and impact area of each flow; and, where possible, comparison of the results obtained from the empirical formulas the results of direct field measurements. It was observed that the various methods at times produce contrasting results. This is attributed principally to the particular characteristics of the studied debris flows, which lie on an open slope and not within a stream bed or valley. It is likely that this type of debris flow requires a different approach from that used with other, better studied types.